Fostering 15–16-Year-Old Students’ Social Responsibility through a Physics E-worksheet: An ENACT Learning Model Intervention - Widiarni, Anggi; Saregar, Antomi; Diani, Rahma; Anugrah, Adyt; Alimin, Masnaini (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
Education in the 21st Century significantly emphasizes developing key competencies, including social responsibility. However, a substantial gap persists between students' theoretical understanding of social responsibility and its practical application, particularly in physics education. This study aims to develop a physics student worksheet based on the ENACT (Engage, Navigate, Anticipate, Conduct, and Take Action) learning model to foster social responsibility among students aged 15 to 16. This study employed the Research and Development (R and D) methodology and adopted the Borg and Gall development model (stages 1–7), involving validation by media and content experts and a practicality assessment. The sample comprised two teachers and 127 students from two public schools in Bandar Lampung, with data collection techniques including structured interviews, observations, and Likert-scale questionnaires. Validation results indicated high quality, with 92% from media experts and 94% from content experts, while practicality assessments yielded scores of 93% from teachers and 89% from students, categorizing the worksheet as highly practical. The teachers and students provided positive feedback, highlighting the worksheet's ease of use, relevance, engaging content, and potential to cultivate social responsibility among students. This study contributes to integrating digital technology into physics education by underscoring the role of interactive learning tools in fostering social responsibility. However, further research is recommended to examine the effectiveness of ENACT-based e-worksheets in diverse educational contexts and across different subject areas.